Klasycy obcy, rodzimi i bohaterowie nekrologów: zainteresowanie przeszłością dyscypliny a perspektywy historii socjologii = Classics - domestic, foreign and obituary heroes: interest in the past of the discipline and the prospects of the history of sociology - Kilias, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is an attempt to assess the prospects of the history of sociology in Poland. Although there seems to be a substantial interest in the history of the discipline among Polish scholars, most of activities labeled as "history of sociology" have in fact nothing to do with history except for discerning and describing what happened in the past. There are probably three major sources of interest in the past of the discipline: classical sociology, foundation myths and celebrative memories of scholars and academic institutions.
Keywords: socjologia - historia